2006
DOI: 10.3354/dao072241
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for widespread distribution of piscidin antimicrobial peptides in teleost fish

Abstract: Antimicrobial peptides (AMPs) are increasingly recognized as a critical component of the host's defense against infection. Several types of AMPs have been recently identified from mucosal tissues or immune cells of a number of teleosts. Among these are the piscidins, which are 22 residue, α-helical AMPs that were originally isolated from mast cells of hybrid striped bass Morone saxatilis male × Morone chrysops female. Using an antibody specific for the conserved N-terminal amino acid sequence of piscidin 1, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
131
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 32 publications
(34 reference statements)
5
131
0
Order By: Relevance
“…In addition, rodlet cells have also been identified as piscidin-positive in one member of the family Cichlidae. This study was the first one which identified in rodlet cells a host-associated chemical biomarker [157]. All piscidins show broad-spectrum antimicrobial activity, probably killing cells via toroidal-pore formation [151,170,171].…”
Section: Antimicrobial Peptidesmentioning
confidence: 83%
See 3 more Smart Citations
“…In addition, rodlet cells have also been identified as piscidin-positive in one member of the family Cichlidae. This study was the first one which identified in rodlet cells a host-associated chemical biomarker [157]. All piscidins show broad-spectrum antimicrobial activity, probably killing cells via toroidal-pore formation [151,170,171].…”
Section: Antimicrobial Peptidesmentioning
confidence: 83%
“…However, several types of AMPs have been identified from mucosal tissues or immune cells of a number of teleosts, and they are, at present, considered a very important part of the mucus and skin barrier function ( [114,157], reviewed by [158]). …”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that although the storage of histamine in MCs and its use as an inflammatory messenger was established in primitive reptiles (Lepidosauria) Ϸ276 mya (44), this same feature developed independently in Perciform fish in the Lower Eocene, between 55 and 45 mya, a short period during which the great majority of Percomorph families appeared (47). It is striking that piscidins had a similar evolutionary history, because only the MCs of Perciformes are endowed with these antimicrobial peptides (48). However, a related family of antimicrobial peptides, called pleurocidins, are synthesized by MCs of the Atlantic halibut (49), a flat fish belonging to the order Pleuronectiformes and the family Pleuronectidae.…”
Section: Discussionmentioning
confidence: 99%